Association of Oral Health Literacy Measured Using the Held-29 With Oral Health Status and Oral Health Behavior Among Independent Older Adults in Depok - Melissa Adiatman; Bernike Dasvitawati; Febriana Setiawati (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Oral health literacy is an important determinant of oral health, particularly among older adults who are vulnerable to oral diseases, tooth loss, and functional decline. This study aims to evaluate the association among oral health literacy, oral health status, and oral health behaviors among independent older people. Materials and Methods: This cross-sectional study involved 195 independent older adults aged 60 years and above in Depok. The subjects completed a self-administered questionnaire collecting information on socio-demographics. Oral health literacy was assessed using the Health Literacy in Dentistry scale with 29 items (HeLD-29), and oral health behavior was assessed using an interviewer-administered questionnaire. Oral health status was recorded by clinical oral examination using the DMF-T index, CPI-modified, denture status, OHI-S, and masticatory performance was assessed subjectively. Results and Discussion: Several HeLD-29 domains were significantly correlated with clinical oral health indicators. Significant differences were found between low and high oral health literacy groups in the number of missing teeth, filled teeth, and deep periodontal pockets (p<0.05). Oral health literacy scores also differed significantly according to age group and educational level (p<0.05). No significant association was found between oral health literacy and oral health behavior. However, DMF-T score was significantly associated with dental visit pattern, and gingival bleeding was significantly associated with smoking status. Conclusion: Oral health literacy was associated with several indicators of oral health status and with sociodemographic factors, particularly age and educational level. An association was also found between oral health status and oral health behavior of independent older adults in Depok.